THEATRICAL PERFORMANCE AND ENGLISH AS A FOREIGN LANGUAGE LEARNING - CAROLINE V. KATEMBA (LPPMPP Institut Seni Indonesia Padangpanjang, 2021)
To understand a foreign language, young learners must first master their vocabulary. As a result, the goal of this study was to determine the efficacy of Theatrical Performance(Role Play Technique) in improving students' vocabulary enhancement. Its specific goal was to answer the question: Is there a significant difference between students who were taught using the Role Play Technique and those who were not taught using Role Play? This was a quantitative study with an experimental using a pre & a post-test design. 68 Students participated in the study. They were divided into the experimental and the control group. According to the findings, there was a significant difference in the vocabulary enhancement of students in the experimental group and the conventional method. Based on the findings of this study, the researcher concludes that using Theatrical Performance or Role Play Techniques can help students improve their vocabulary